Implementation of cybergogy learning using artificial intelligence in enhancing learning outcomes - Rusdiyah, Farda Hidayatul (Maliki Interdisciplinary Journal, 2024)
This study explores the role of artificial intelligence (AI) in improving learning outcomes through a cybergogy approach, which is a combination of pedagogy, andragogy, and heutagogy in a digital environment at SMP Darul Fikri Ngoro Jombang. This study used a qualitative research approach with a case study design. Data were obtained through in-depth interviews with the principal, vice principal for Curriculum, 7 educators, 12 students, and 3 technology developers, as well as document analysis and direct observation. The results showed that AI has good potential in enriching learning experiences, personalizing learning, and increasing student engagement. The application of AI in cybergogy helps in providing adaptive learning materials, real-time feedback, and learning support tailored to students’ individual needs. In addition, AI is also instrumental in identifying learning gaps and offering timely interventions, which contribute to improved student academic outcomes.